Development of single row automatic transplanting device for potted vegetable seedlings - Jin, Xin; Li, Daoyi; Ma, Hao; Ji, Jiangtao; Zhao, Kaixuan; Pang, Jing (International Journal of Agricultural and Biological Engineering, 2018)
In China, low degree of automation seriously affects the working efficiency and quality in vegetable transplanting. As one of the most important vegetables in China even in the world, tomato was taken as the research object in this study. An automatic single-row transplanting device was designed, based on the statistical analysis of the physical and mechanical properties of tomato seedlings of a typical variety. Based on the technology of mechatronics, the device integrated the functions of transporting seedling tray, automatic seedling extraction and mechanical planting. The kinematics orthogonality solution combined with the dynamic sequence solution method was used to optimize and analyze the kinematic parameters of the automatic seeding mechanism, and the “sickle” trajectory was obtained. According to the position and movement requirement for taking and dropping seedling, the mechanical conditions and the working parameters of key execution parts were obtained by using analytic drawing method to analyze the mechanical condition of seedling collecting mechanism. The transplanting experiment was conducted at room temperature of 25°C, and the age and moisture content of the seedlings were 40 d and 55%, respectively. The results showed that the highest success rate was 92.59%, and the lowest rate of leakage was 23.13%, when the transplanting frequency was 60 plants/min. The lowest success rate was 77.78%, and the highest rate of leakage was 38.75%, when transplanting frequency was 120 plants/min. When the transplanting frequency is between 60-90 plants/min, the device can meet the requirement of high speed transplanting for potted vegetable seedling.Keywords: potted vegetable seedling, seedling mechanism, automatic transplanting, tomato seedling, transplanting experimentDOI: 10.25165/j.ijabe.20181103.3969Citation: Jin X, Li D Y, Ma H, Ji J T, Zhao K X, Pang J. Development of single row automatic transplanting device for potted vegetable seedlings. Int J Agric & Biol Eng, 2018; 11(3): 67–75.